Quantitation of pH- and salt-tolerant subpopulations from Clostridium botulinum. - Montville, T J (1984)
Plating efficiencies of Clostridium botulinum 62A spores on media with variable pH (7.0 to 5.5) and salt (0, 1, 2, and 3%) levels revealed that only a very small subpopulation could give rise to colonies. The relative size of this subpopulation decreased by orders of magnitude with decreasing pH and increasing salt concentrations. Strong interactions of pH with salt were noted. For example, on a medium containing 2% salt at pH 5.5, colonies could be formed from only 1 in 100,000 spores. Proper monitoring of medium anaerobiosis was critical in obtaining reproducible results.